A comparative study on traditional mask of Mah Meri Tribe and Awang Batil / Wan Maryam Nabihah Wan Mohd Zukri - Wan Mohd Zukri, Wan Maryam Nabihah (2019)
This paper studies on the comparison between traditional mask of Mah Meri tribe and Awang Batil. In this modernization era, traditional mask has not been that well known in Malaysia. Due to minimal usage of traditional mask, the younger generations are missing out on this cultural heritage. Therefore, this research paper is going to explore and understand more about traditional mask in Malaysia, in the past and present, its usage and purpose, as well as the differences of traditional mask between Mah Meri tribe and Awang Batil which is the community that are still actively using traditional mask up to these days. The objective of this research is to study the design and content of traditional mask of Mah Meri tribe and Awang Batil while identifying their differences through a comparison. The data collection of this research was held at several places such as Muzium Orang Asli in Gombak, Muzium Seni Kraf Orang Asli in Kuala Lumpur and Mah Meri Cultural Village in Carey Island. This research also holds literature reviews of past studies on the traditional masks. A comparison between the traditional masks will be made as it holds answers to the decreasing usage of mask culture in Malaysia and its relations with the traditional mask design itself. Before the comparison was made, this research will first study on the research methodology and how to analyse the data that had been gathered by the researcher. The researcher found out and believe that the differences between traditional mask of Mah Meri and Awang Batil are the keys to unlock more ways to preserve this cultural heritage.